The liver protection and antioxydant effects of silymarin extracted from milk thistle Silybum marianum (L.) Gaertn - To Nga, Nguyen Thi; Tuyen, Do Thi; Viet, Doan Van; Ngoc Dao, Nguyen Thi (Academia Journal of Biology, 2014)
Milk thistle - Silybum marianum (L.) Gaertn. belongs to the family Asteraceae. It is a herb living from one to two years. Is herb lives mainly in Europe, Africa, South America, Middle and East Asia. Now, it is introduced and planted in many regions of Vietnam that have good soil and fresh climate as Tamdao, Sapa. It is used to treat hepatic and kidney diseases mostly, antioxidant and other diseases. A standardized extract of milk thistle contains at least 70% silymarin, a mixture which contains flavonolignans (silybin, isosilybin, silychristin, silydianin). Among them, silybin is a compound which has pharmatical activity mainly in the effect of silymarin. We have experimented on the liver protection and antioxydant effects of silymarin. The result indicated that silymarin effected on the P450 enzyme system of live rats. The treatment with silymarin (0,1mg/g W/day), after 10 days, increased the P450 amount (25%) but reduced the activity of the aniline hydroxylase and the cytochrome P450 reductase enzymes. With the rats that were toxicited by CCl4, silymarin had active change compared to the simple toxical rats. Silymarin had also the antioxydant effect on the toxicated rats by activating the SOD and GPx enzimes at the same time improved the total antioxydant status.